(untitled) (Palíndromo, 2020)
The present study aims to present the results of a practical-theoretical research about dance in digital culture, proposing the experience of creation in dance and technology. In order to understand the specificities of creation of the area, bibliographical researches were developed from Ivani Santana and Isabel Maria de Cavadas Valverde, as well as researches with software and applications for smartphones, resulting in the show ‘Trilha’. From the aspects pointed out by these authors, this study makes an analysis about the creation of the show and presents reflections about the technological poetics used by it. It is understood that the practical-theoretical character combined with the production of a show helps in the extension of the ways of receiving an academic study in arts, as well as expands the places of discussion and the reach of the theme.